The Effect of Concentrations Coconut Water on Growth and Yield Plant Cutting of Mint - Muhammad Yudhy Octoarie; Dini Anggorowati; Astina . (Jurnal Sains Pertanian Equator, 2020)
This study aims to determine the best concentration of coconut water on growth and yield plan cutting of mint. This study held from on February 25st to April 25th 2019. The research was conducted in Purnama Agung VII, Komplek Pondok Agung Permata, South Pontianak. The method use is randomized completely design of one factor,the treatment consisted of 5 treatments, namely (p1 = concentrations of coconut water 0%, p2 = concentrations of coconut water 12,5%, p3 = concentrations of coconut water 25%, p4 = concentrations of coconut water 37,5%, p5 = concentrations of coconut water 50%,) all treatmets were repeated 5 times, each treatment consisting of 4 plant samples. The results showed that the concentrations of 25% coconut water was the best concentration for improving yield of cuttings of mint plants.Keywords: Coconut Water, Plant Cutting of Mint.